LEVEL OF MOTION EFFICIENCY OF STUDENTS AT FCHPT STU IN BRATISLAVA (Fiep Bulletin - online, 2014)
The aim of work was to find out and consequently compare the level of motion efficiency and level of somatic development  of the 1.st academic year students (2012/2013) Faculty of chemical and food technology STU in Bratislava (122 men and 382 women). Acquired results of explored collection we compared with the results of the 1.st academic year students in 2011/2012 at FCH PT STU in Bratislava. We observed statistic distinctions also in the collection itself. We divided all testing group in particular sections according some predetermined criteria. These criteria were regions they come from, type of graduated secondary school and the fact if the student is or is not a sportsman. To discover motion efficiency we used standardized motion test batteries. To discover somatic level development we used BMI index. From the results of testing motion efficiency is clear, there are not any significant distinctions in dividing the group according regions and secondary schools in the men category. I n the women category we found out some significant distinctions only by dividing the group according regions. Lady students from Bratislava and the Central Slovak region dominated in upper limb strength. In the case of dividing the group according “sportsman” or “non-sportsman” we found out significant distinctions in both men and women categories prosperous for sportsmen. At the level of somatic development we did not observe any significant distinctions in any group dividing. At the results comparison of motion testing efficiency and somatic level development of students of the 1.st academic year 2011/12 and 2012/13 we found out significant distinctions in sit-ups (both men and women) prosperous for year 2012/1013. On the other side we found out significant distinctions non prosperous for the year 2012/2013 in beep test of women. In the level of somatic development of both men and women we found out significant distinctions in BMI value index. The number of lady students with underweight came down but on the other side the number of lady students with overweight came up. At the male students there was a significant increase of students with underweight and decline of students with overweight.
Keywords: motion efficiency; criteria; testing; comparison of results